OSL, RL and TL characterization of rare-earth ion doped K2YF5: Application in dosimetry - Marcazzo, Salvador Julian (2011)
Optically stimulated luminescence (OSL) properties of K2YF5 crystals singly doped with different concentrations of Tb3þions and doubly doped with Tb3þand Ce3þor Tb3þand Dy3þhave been investigated for the first time. Radioluminescence spectra and OSL efficiency for stimulation with different wavelengths of light have been analyzed for each compound. Also, dosimetric characteristics of the most efficient composition, namely K2YF5:1 at.% Tb3þ, have been studied. Finally, the OSL signal peculiarities for K2YF5:1 at.% Tb3þhave been compared to those of a commercial Al2O3:C dosimeter.